PENGAKUAN DAN IMPLEMENTASI HUKUM ADAT PERKAWINAN SUKU BUGIS DALAM STUDI POLITIK HUKUM NASIONAL - Sayid Anshar; Baso Ifing (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study departs from the reality of legal pluralism in Indonesia, where the customary law of marriage among the Bugis tribe as living law interacts dynamically with national marriage law, which is unified through Law No. 1 of 1974. On the one hand, Bugis customary marriage law is rich in unique philosophical values and social institutions, such as siri' na pesse (pride and solidarity), mahar (sompa), and shopping money (uang panai') which are often the main determinants of the social validity of marriage. On the other hand, national law requires registration as formal proof of legality, which often creates tension and legal problems for indigenous peoples. This abstract underlines the urgency of legal policy analysis to examine how the state addresses this dualism. The purpose of this study is to analyze the direction of the state's legal politics in accommodating the customary marriage laws of the Bugis tribe, as well as to map the points of synchronization and conflict between customary norms and national law, in order to understand the legal and sociological implications for society. This study uses a legal-empirical method with a legal political and legal sociological approach. Data was obtained through literature study, analysis of legislation, and in-depth interviews with customary leaders, legal practitioners, and the Bugis community. The results of the study show that the state's legal policy is ambivalent. On the one hand, the state gives semi-formal recognition to Bugis customary marriage through the mediating role of the KUA and courts that accommodate several customary elements. On the other hand, the dominance of the unifying Marriage Law creates legal uncertainty, which has an impact on the legal status of children and the civil rights of women. This ambivalence is influenced by the tension between the ideology of a unitary state and the pressure to recognize legal pluralism after the Reformation. Keywords: Legal Politics, Customary Law, Traditional Marriage, Bugis Tribe, Legal Pluralism